Violent conflict, terrorism, and nation-building : national and international responses in Sri Lanka and other South Asian countries - De Silva, K. M.; International Centre for Ethnic Studies (Kandy : International Centre for Ethnic Studies, 2009)
Contributed articles presented in a workshop, organized by ICES, held during Aug. 3-4, 2007, in Kandy, Sri Lanka.
Keywords: Terrorism -- South Asia -- Congresses; Nation-building -- South Asia -- Congresses